PP68 Sexual risk behaviours among young people in rural mwanza, tanzania: is marriage protective?. (31st August 2015) - Doyle, AM; Changalucha, J; Weiss, HA; Watson-Jones, D; Hayes, RJ; Ross, DA
Abstract : Background: Traditionally marriage has been considered a safe context in which to have sexual relations. However, research in adults has shown that risk of infection with HIV and other STIs can be high within marriage. We investigated risk behaviour within different types of sexual partnerships reported by young people in Tanzania. Methods: In 2007/8 in 20 communities of rural Mwanza Region, Tanzania, sexual partnership histories of 13, 814 young people aged 15–30 years were collected through a face-to-face questionnaire. Participants reported on their most recent sexual partners in the previous 12 months, up to a maximum of 3. We analysed data on 16, 623 partnerships reported by 11, 301 participants. Participants who were living with a man/woman as wife/husband were included as married. Participants described their sexual partners as spousal, regular, casual or sex worker. Chi-squared and Wald tests were used to calculate p-values. Results: The mean age in the study was 21 years. A third of males (34%) and over half of females (57%) were currently married and 9% females and 3% males were previously married. Of those currently married, 13% of females reported that their husband had other wives and 2% of males reported more than one wife. A small proportion (6%) of currently married females reported >1 sexual partner in the previous 12 months. However, reports of multiple partnerships in the previous 12 months were high among married males (49%) and previously married individuals (females 34%; males 75%). In almost half of spousal partnerships but only 20% of other regular/casual partnerships there was at least a 4 year age difference between partners. Participants reported having used a condom at last sex with only 5% of their spousal partners compared to 45% of their other partners (p < 0.001). Mean and median (IQR) coital frequency in the last 4 weeks were 5 and 3 (1, 6) with spousal partners and 1 and 0 (0, 1) with other partners (p < 0.001).  Conclusion: Young people report less condom use and a higher frequency of sex with their spousal partners. High levels of multiple partnerships reported by men and large age differentials in spousal partnerships suggest that risk of transmission of HIV and STIs within marriage is likely to be high. Interventions are needed to help married and previously married young people manage risk of HIV/STIs within their partnerships.